Prostatic Abscess a Diagnostic Dilemma - Agarwal, A; Praveen, C R; Hirachan, S; Karmacharya, A; Belokar, W K (Journal of Nepal Health Research Council, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Abscess of the prostate has become increasingly rare due to modern antibiotics and a decreasing incidence of gonococcal infections. It is still difficult to diagnose the disorder on clinical grounds. Diagnosis is often made after Ultrasound examination. We report 2 cases of prostatic abscess and review etiopathogenic factors, clinical findings, diagnosis and treatment of this uncommon entity. Â Key words: abscess, diagnosis,etiopathogenesis,prostate, therapeutics